REKAYASA BIOSAFETY CABINET MENGGUNAKAN STERILISATORULTRAVIOLET DAN EVAPORASI CAIRAN DESINFEKTAN - Sigit Widadi (Jurnal Riset Teknik Komputer, 2024)
This article presents the results of the engineering research on the Biological Safety Cabinet (BSC) which is commonly used in medical sample laboratories to protecting the workers and ensure that no dangerous infectious agent material escapes from the cabinet. This research used a combination technique of ultraviolet (UV) sterilization and evaporation of disinfectant liquid, the duration and discharge of each method can be controlled. The selection of UV light source power, air circulation flow and disinfectant liquid rate takes into account of the size of the BSC work space. The method used in this research is integrating the ATMega328P module, anemometer sensor module, mist maker module and solid state relay (SSR) module. The test of parameters used are the level of UV light radiation, air circulation discharge and the relative humidity level of air exposed to disinfectant liquid mist in the BSC work space. Testing is carried out by taking data for each parameter. Next, the test data is analyzed based on literature references to determine of he feasibility and classification of the engineered BSC